Promoting Physical Activity at Primary Health Care Centers: Physician Attitude and Barriers, Jazan-Saudi Arabia - Hassan, Hamood Mohammed Mohammed; Hakami, Mohammed Ibrahim; Mahfouz, Mohamed Salih (Journal of medical and pharmaceutical sciences, 2018)
Objectives: To assess the attitude of primary health care physician regarding promoting regular physical activity; to identify the perceived barriers which can affect promoting regular physical activity and to identify the factors associated with promoting regular physical activity. Subjects and methods: This is a cross-sectional study carried out from March 2017 to Jun 2018. Self-administered questionnaires were administered to primary health care physicians. Results: The study included 140 (60.1%) males and 93 (39.9%) females with a total number of 233 physicians. Most of physicians had positive attitudes towards promoting physical activity in PHC as above 80 % of them either agreed or strongly agreed on the positive statements of Likert scale. The highly prevalent barriers of effective physical activity promotion as perceived by the participants were insufficient educational materials (79.4%), lack of compliance of patients (78.5%), lack of standard protocols (76.4%), and lack of available education for health professionals regarding physical activity promotion (75.5%). There were no significant differences between males and females regarding the overall attitude score and all items of the Likert scale. Conclusions: This study shows that the majority of PHC physicians, regardless their age, sex, nationality, marital status, years of experience and job titles had highly positive attitude towards promoting physical activity in PHCCs.